2022
DOI: 10.1108/jgoss-03-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the interactions of sustainability practices and financial performance on business-to-business buying behaviour in Indian manufacturing industry: a graph-theoretic approach

Abstract: Purpose This study aims to develop a framework for the action hierarchy of sustainability practices and financial performance and their optimal combination for supplier evaluation and selection in business-to-business (B2B) for the Indian manufacturing industry. Design/methodology/approach Through the extensive literature review followed by comprehensive interviews conducted using the Delphi methodology with professionals, this study attempts to represent the interactions of the sustainability practices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…For example, the use of biodegradable and recyclable products and packaging, and services and products that are not responsible for excessive greenhouse gasses due to the utilization of renewable raw material and energy in their production [12][13][14]. A number of studies propose further research on greener and/or more sustainable environmental approaches [15][16][17][18][19][20][21][22][23][24][25][26][27]; hence, organizations should implement and develop sustainable procurement practices, which should include strategies, guidelines, and procedures to assist with more environmentally friendly and sustainable procurement decisions [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, the use of biodegradable and recyclable products and packaging, and services and products that are not responsible for excessive greenhouse gasses due to the utilization of renewable raw material and energy in their production [12][13][14]. A number of studies propose further research on greener and/or more sustainable environmental approaches [15][16][17][18][19][20][21][22][23][24][25][26][27]; hence, organizations should implement and develop sustainable procurement practices, which should include strategies, guidelines, and procedures to assist with more environmentally friendly and sustainable procurement decisions [12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of research gaps were identified based on the above B2B procurement, supplier, and TBL discourse. Saxena and Seth [23] suggested that further research was needed to investigate TBL substantiality issues. Boruchowitch and Fritz [50] confirm that more research is required based on sustainable SCM and procurement.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations